HUMAN DIGNITY IN AFRICA: A CHRISTOLOGICAL APPROACH - Koopman, Nico (Scriptura, 2010)
The violation of human dignity is more acute on the continent of Africa than in most other places in the world. In this article the dehumanizing influence of a wide range of factors is considered: amongst others growing inequality, violence, illness and various forms of prejudice. It is then argued that insights from the Christology of John Calvin provide avenues for restoring human dignity in Africa, and that his work on the threefold office of Christ may prove to be particularly helpful.